Blood transcriptomic profiles associated with fatal melioidosis and type 2 diabetes induced susceptibility to intracellular pathogens - Rongkard, P (2022)
Background: Melioidosis is caused by the Gram-negative bacterium Burkholderia pseudomallei, and is a leading cause of death from community-acquired infections in Northeast Thailand with a case fatality rate of up to 50%. Most melioidosis patients have one or more comorbidities, and more than half of patients have diabetes which confers a 12-fold increased susceptibility to melioidosis. A similar, but less marked, relationship is seen in tuberculosis (TB) patients, with a 3-fold increased risk of developing TB in people with diabetes. Little is known regarding the mechanisms underlying the increased susceptibility in diabetes to these intracellular pathogens. Likewise, the host response associated with fatal melioidosis remains to be fully elucidated.